A distributed control based coordination scheme of household PV systems for overvoltage prevention - Reeves, D.; Nourbakhsh, G.; Mokhtari, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2013)
This paper presents a distributed communication based active power curtailment (APC) control scheme for grid connected photovoltaic (PV) systems to address voltage rise. A simple distribution feeder model is presented and simulated using MATLAB. The resource sharing based control schemeproposed is shown to be effective at reducing voltage rise during times of peak generation and low load. Simulations also show the even distribution of APC using simple communications. Simulations demonstrate the versatility of the proposed control method under major communication failure conditions. Further research may lead to possible applications in coordinated electric vehicle (EV) charging.